Tinjauan Fikih Siyasah Terhadap Keterwakilan Perempuan pada Badan Permusyawaratan Desa (Tuha Peut) - Sarah Nazlia (TANFIDZIY, 2022)
Qanun of Pidie Jaya Regency Number 2 of 2018 Article 95 paragraph (1) states that the filling of tuha peut membership is carried out democratically through a direct election process or representative deliberation 0by guaranteeing the representation of the hamlet area and the representation of women. Seeing these rules, every gampong should implement the rules made by the government, where each gampong elects 1 (one) woman as a tuha peut member. This type of research is qualitative research. The approach in this study is descriptive, namely an in-depth method of a subject of thought. Data processing used is observation, interview results and documentation. The results of the study show that the fact that women's representation in tuha peut in the village of Kuta Krueng, Bandar Dua District, Pidie Jaya Regency has not fully paid attention to women's representation. Currently there is not a single woman in the tuha peut membership. In the view of siyasa fiqh, a government institution should comply with the rules that have been made and in Islam it does not prohibit women from becoming community representatives or leaders as long as they are able and willing to be nominated.